2017
DOI: 10.1371/journal.pone.0185253
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis of pituitary glands from Huoyan geese between pre-laying and laying periods using an iTRAQ-based approach

Abstract: In this study, we performed a comprehensive evaluation of the proteomic profile of the pituitary gland of the Huoyan goose during the laying period compared to the pre-laying period using an iTRAQ-based approach. Protein samples were prepared from pituitary gland tissues of nine pre-laying period and nine laying period geese. Then the protein samples from three randomly selected geese within each period were pooled in equal amounts to generate one biological sample pool. We identified 684 differentially expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…As in our previous report, the expression of ITPR3, a member of the family of inositol 1,4,5‐trisphosphate (IP 3 ) receptors, was found to be down‐regulated in hypothalamus tissue from Huoyan geese during the laying period (Luan et al., ). IP 3 is an intracellular second messenger that transduces neurotransmitter signals.…”
Section: Discussionmentioning
confidence: 52%
“…As in our previous report, the expression of ITPR3, a member of the family of inositol 1,4,5‐trisphosphate (IP 3 ) receptors, was found to be down‐regulated in hypothalamus tissue from Huoyan geese during the laying period (Luan et al., ). IP 3 is an intracellular second messenger that transduces neurotransmitter signals.…”
Section: Discussionmentioning
confidence: 52%
“…iTRAQ is one of the most advanced technology in modern quantitative proteomics [21, 22]; it combines stable isotope labeling with tandem mass spectrometry [2325] to compare the relative amount of proteins from normal and diseased samples in a single experiment. Wang WS et al [26] revealed that myoferlin is a novel prognostic predictor in pancreatic adenocarcinoma through iTRAQ-based quantitative proteomics.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in this network, casein kinase 2 alpha 2 (CSNK2A2) is down-regulated in the pituitary of HEPH during the PS. CSNK2A2 encodes an uncharacterized protein in avian species but this protein was shown to be decreased in laying geese pituitaries when compared to non-laying geese, indicating a possible role in egg production or ovulation [17].…”
Section: The Hpg Axismentioning
confidence: 99%